Analisis Implementasi Kebijakan Penerbitan Surat Keterangan Asal Elektronik Di Instansi Penerbit Surat Keterangan Asal (Ipska) Kantor Walikota Jakarta Timur - Asep Ishak Farid; Krishantoro Krishantoro (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The implementation of the policy of certificate of origin issuance at the IPSKA in the Mayor Office of East Jakarta has been running well, however, it requires some improvement in several aspects that are still lacking. The description of (1) aspect of communication, Communication of policy information has been carried out to the company by electronic media and by other circular letters. However, consistency from the government is important in this implementation in order to avoid confusion from users. (2) The aspect of resources, the staff of IPSKA do not have a uniformed regulation understanding, therefore socialization and seminars on electronic SKA issuance policy regulation are necessary. Additionally, facilities and infrastructures have to be improved further to simplify and expedite the operation of issuing certificates electronically. (3) The aspect of Disposition, in this case, the government has shown a commitment to policy implementation. However, there are several things to improve in terms of system and other aspects in order to be able to protect service users in implementing their policies. (4) The aspect of Bureaucratic, the authority flow of electronic Certificate is quite clear, however, a written SOP is required in implementation in order to measure the implementation clearly and precisely.